2013
DOI: 10.4067/s0716-97602013000100010
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of nucleolar chromatin distribution in the complex convoluted nucleoli of Didinium nasutum (Ciliophora)

Abstract: We have earlier shown that the typical Didinium nasutum nucleolus is a complex convoluted branched domain, comprising a dense fi brillar component located at the periphery of the nucleolus and a granular component located in the central part. Here our main interest was to study quantitatively the spatial distribution of nucleolar chromatin structures in these convoluted nucleoli. There are no "classical" fi brillar centers in D.nasutum nucleoli. The spatial distribution of nucleolar chromatin bodies, which pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The nucleolus is a highly dynamic subnuclear domain where rRNA synthesis, rRNA processing and assembly of ribosomal subunits take place [26]. It plays important roles in the regulation of many fundamental cellular processes, including cell cycle regulation, apoptosis, telomerase production, and the monitoring and response to cellular stress [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…The nucleolus is a highly dynamic subnuclear domain where rRNA synthesis, rRNA processing and assembly of ribosomal subunits take place [26]. It plays important roles in the regulation of many fundamental cellular processes, including cell cycle regulation, apoptosis, telomerase production, and the monitoring and response to cellular stress [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Using three-dimensional electron microscopy reconstructions, it has been shown that D. nasutum nucleoli, looking on the single sections like individual separate structures, are parts of the large complicated branchy nucleolar networks (Leonova et al, 2006(Leonova et al, , 2012(Leonova et al, , 2013. 3D models built on the basis of serial ultrathin sections show that in these nucleolar domains the fibrillar component is located at the periphery, while the granular part is in the central part of the nucleolus (Leonova et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrillarin homologues are present in the cells of various species from Archaea to human (Henriquez et al, 1990;Amiri, 1994;Amin et al, 2007). Fibrillarin plays an important role in early processing and modification of pre-rRNA, ribosome assembly, and is also essential for early embryonic development (Fomproix et al, 1989;Tollervey et al, 1993;Newton et al, 2003). Moreover, fibrillarin plays a critical role in the maintenance of nuclear shape and cellular growth (Amin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that in "gene-sized" species Stylonychia lemnae rRNA is processed in a bipartite and inverse manner compared to a typical metazoan nucleolar organization (Postberg et al, 2006). The nucleoli of another ciliate, Didinium nasutum, also display the bipartite structure, with an inverted disposition of its main components (Leonova et al, 2006(Leonova et al, , 2012(Leonova et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%